Phylogenetic patterns of trait and trait plasticity evolution: Insights from tadpoles. (1st October 2021) - Relyea, Rick A.; Stephens, Patrick R.; Hammond, John I.
Abstract: Environmental heterogeneity has led to the widespread evolution of phenotypic plasticity in all taxonomic groups. Although phenotypic plasticity has been examined from multiple perspectives, few studies have examined evolutionary patterns of plasticity within a phylogeny. We conducted common‐garden experiments on 20 species of tadpoles, spanning three families, exposed for 4 weeks to a control, predator cues, or reduced food (i.e., increased intraspecific competition). We quantified tadpole activity, growth, and relative morphology and found widespread differences in species responses to predator cues and reduced food. We detected pervasive phylogenetic signals in traits within each environment, but the phylogenetic signal was much less common in the trait plasticities. Among different models of continuous character evolution, Brownian Motion and Ornstein Uhlenbeck models provided better fits to the data than the Early Burst model. Tadpole activity level in predator environments had much higher evolutionary rates than in the control and reduced‐food environments; we did not see this pattern in the other traits. In comparing traits versus trait plasticities, activity evolved much faster than the plasticity of activity whereas morphological traits evolved much slower than morphological plasticities. Collectively, these results suggest that traits and trait plasticities can exhibit dramatically different evolutionary patterns.